SAINS TERBUKA (OPEN SCIENCE) DAN DEKOLONISASI PENGETAHUAN: STUDI KASUS ILMU SEJARAH - Supratman, Frial (BACA: Jurnal Dokumentasi dan Informasi, 2024)
Since the nineteenth century, social and humanities sciences had been predominantly dominated by Western scholars. Many Western scholars traveled to Asia, the Middle East, and Africa, gathering data from local sources in order to develop theories from their perspectives. Unfortunately, those theories were uncritically accepted by local scholars, applied in local cases and problems. The domination of social and humanities sciences by Western academia attracts “Third World” scholars to criticize it. They urge local scholars to decolonize Western-centric theories and concepts which have been imitated and applied in local problems without criticism. In this article, the author investigates the role of Sains Terbuka (Open Science) on decolonizing humanities science in Indonesia and Turkey. The author only observes history science as a case study rather than investigating all branches of social and humanities sciences. In this article, the author uses descriptive-analytic method through the historical approach, gathering data from literature and scientific journals to analyze attempts of Indonesian and Turkish scholars to oppose Western Centric theories and concepts. The author also explains that the rise of digital-based history sources plays a vital role in supporting the decolonization of knowledge and Sains Terbuka in Turkey and Indonesia. This research collects several online and digital-based history sources, such as the Khastara National Library of Indonesia collection and ISAM Library collection that have been often used by Indonesian and Turkish historians for their research. In this article, the author argues that open access of digital sources is highly important for historians to gather myriad data in local languages, encouraging them to create new theories and concepts that are free from Western Centric views.